Boosting visible light photo-/Fenton-catalytic synergetic activity of BiOIO3 by coupling with Fe2O3. Issue 38 (3rd May 2017) - Zeng, Hehua; Liu, Xiu; Wei, Ting; Li, Xueqin; Liu, Tianxiang; Min, Xuemei; Zhu, Qiuhui; Zhao, Xiufeng; Li, Jianhui
Abstract : BiOIO3 and Fe2 O3 can couple in one-step and show visible photocatalytic and heterogeneous Fenton-like synergetic activity for p -nitrophenol degradation. Abstract : The combination of a semiconductor photocatalyst with guest transition metal oxides can extend its light absorption property in the visible region, leading to the emergence of potential catalysts for solar photocatalytic degradation. In the present study, Fe2 O3 /BiOIO3 nanosheets with heterojunction couples have been fabricated in one-step by a simple hydrothermal method and used as a heterogeneous Fenton-like photocatalyst for the oxidative degradation of p -nitrophenol (PNP) under visible light. The absorption range of BiOIO3 extended to the visible light region with the introduction of Fe, while the band gap is dramatically decreased from 3.00 eV for pure BiOIO3 to 1.81 eV for 30% Fe2 O3 /BiOIO3 . The recombination of photogenerated electron–hole pairs can also be prevented effectively. The intrinsic relationship between structure and catalytic activity was fully studied and a possible catalytic mechanism was proposed. The enhanced photocatalytic activity can be attributed to the synergistic effect of heterojunction semiconductor photocatalysis and heterogeneous Fenton catalysis caused by BiOIO3 and Fe2 O3 . This highly active heterogeneous catalyst has the potential for efficient utilization of solar energy in the visible range and can be applied in environmental remediation and waste water treatment.